Self-consistency and congruence, perceived social support, and psychological resilience as predictors of professional identity of male nursing students among consecutive secondary and higher vocational education - Ma, Li; Sun, Xu; Zhou, Wei; Lin, Zhenpeng; Li, Anqi; Kong, Fanqun; Xue, Yuchen; Dong, Zhouyan; Wu, Yulong; Cheng, Mei (Frontiers in Psychology, 2025)
ObjectiveConsidering the traditional female nature of the nursing field, male nursing students often experience a strong urge to leave the profession. A robust professional identity (PI) is crucial for male nurses, as it can alleviate professional stress and enhance their willingness to remain in the field. Among full-time nursing vocational education programs, the consecutive secondary and higher vocational nursing (CSAHVN) stands out for offering comprehensive and advanced professional education, leading to the cultivation of highly skilled nurses. Nevertheless, the predictive factors influencing male nursing students’ PI during their CSAHVN education remain poorly understood.MethodsConvenience sampling was used to recruit male students in the CSAHVN education from two vocational schools. Data on PI, self-consistency and congruence, perceived social support and psychological resilience were collected using questionnaires.ResultsThe average score for male nursing students’ PI was 3.85 (SD = 0.68). The total scores and sub-dimensions of self-consistency and congruence, perceived social support, and psychological resilience demonstrated significant correlations with PI. Multivariate analyses identified motivation and interest in nursing profession, along with sub-dimensions of self-consistency and congruence (self-flexibility), psychological resilience (tenacity), and perceived social support (family support) (p < 0.01) as principal predictors of the PI among male CSAHVN students, with three-dimensional scatter plots demonstrating superior predictive capacity of tenacity and self-flexibility.ConclusionOur findings underscore the necessity for systemic interventions in educational innovations that strengthen professional commitment and foster family-school collaboration to enhance tenacity and self-flexibility, which are essential to counteract gender stereotypes and thereby increase the PI of male students in CSAHVN education.